ANALYSIS OF LEARNING CONCEPTS - fitriani syamal; Neviyarni (Yayasan Citra Dharma Cindekia, 2021)
This article discusses concept learning analysis which includes the nature of concept learning, concept learning studies, factors that influence concept learning, concept learning theory, and practical principles about concept learning. Concept learning refers to all activities in which learners must learn to group two or more different objects or events into one category. Learning concepts is also learning to make the same response in groups to stimuli that have the same form. The study of learning concepts includes a stimulus response, and some feedback to students.